Crafting Business Strategy for Future Development of Merdeka 8 Coffee and Resto using Diamond Strategy Framework (The Indonesian Journal of Business Administration, 2015)
Abstract.Merdeka 8 is a coffee shop located in Kalimalang, East Jakarta. Merdeka 8’s target market is young people in Kalimalang area with motorcycle as their daily transportation. Today, Merdeka 8 gains new target market, car user customers. The problem is that the parking lot cannot facilitate the new market. This research is aimed to find best solution and strategy for Merdeka 8’s in the future. Moreover, this research will assist Merdeka 8 to define their arena, explore the require differentiator, plan their staging, choose the vehicle, and evaluate the economic logic in order to convey Merdeka 8 as a leader in the industry and the recommendation made by this research would improve their performance in the future. The research will conduct business strategy diamond, PEST analysis, Porter’s Five Forces, Value Chain Analysis, SWOT, cluster analysis to segmentation existing and potential customer, Business model, strategic moves, examine cost and Merdeka 8’s ability.Keywords: Coffee shop business, business strategy, Diamond Strategy